Genotypic status of the TbAT1/P2 adenosine transporter of Trypanosoma brucei gambiense isolates from Northwestern Uganda following melarsoprol withdrawal. - Anne J N Kazibwe; Barbara Nerima; Harry P de Koning; Pascal Mäser; Michael P Barrett; Enock Matovu (Public Library of Science (PLoS), 2009)
Background The development of arsenical and diamidine resistance in Trypanosoma brucei is associated with loss of drug uptake by the P2 purine transporter as a result of alterations in the corresponding T. brucei adenosine transporter 1 gene (TbAT1). Previously, specific TbAT1 mutant type alleles linked to melarsoprol treatment failure were significantly more prevalent in T. b. gambiense from relapse patients at Omugo health centre in Arua district. Relapse rates of up to 30% prompted a shift from melarsoprol to eflornithine (alpha-difluoromethylornithine, DFMO) as first-line treatment at this centre. The aim of this study was to determine the status of TbAT1 in recent isolates collected from T. b. gambiense sleeping sickness patients from Arua and Moyo districts in Northwestern Uganda after this shift in first-line drug choice. Methodology and results Blood and cerebrospinal fluids of consenting patients were collected for DNA preparation and subsequent amplification. All of the 105 isolates from Omugo that we successfully analysed by PCR-RFLP possessed the TbAT1 wild type allele. In addition, PCR/RFLP analysis was performed for 74 samples from Moyo, where melarsoprol is still the first line drug; 61 samples displayed the wild genotype while six were mutant and seven had a mixed pattern of both mutant and wild-type TbAT1. The melarsoprol treatment failure rate at Moyo over the same period was nine out of 101 stage II cases that were followed up at least once. Five of the relapse cases harboured mutant TbAT1, one had the wild type, while no amplification was achieved from the remaining three samples. Conclusions/significance The apparent disappearance of mutant alleles at Omugo may correlate with melarsoprol withdrawal as first-line treatment. Our results suggest that melarsoprol could successfully be reintroduced following a time lag subsequent to its replacement. A field-applicable test to predict melarsoprol treatment outcome and identify patients for whom the drug can still be beneficial is clearly required. This will facilitate cost-effective management of HAT in rural resource-poor settings, given that eflornithine has a much higher logistical requirement for its application.